Persepsi Siswa terhadap Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan di SMA Negeri 1 Simpang Empat - Jan Bobby Nesra Barus; Janwar Frihasan Sinuraya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The narrow perception of physical education causes the goals of education contained therein to not achieve goals. Perceptions of each individual will be different and influenced by factors, this basis makes researchers interested in knowing the perceptions of students in SMA Negeri 1 Simpang Empat on physical subjects. The purpose of this study was to analyze students' perceptions of learning physical education, sports and health at SMA Negeri 1 Simpang Empat. This study used a survey method, the population was 42 students of class X and XI. Data collection techniques using questionnaires and google forms as a tool. Data analysis with Correlation Product Moment and SPSS 20. The results showed the perceptions of students in class X and XI at SMA Negeri 1 Simpang Empat with 42 respondents that the students' perceptions in participating in learning physical sports and health were included in the good category as many as 26 people. or 61.90%, the very good category was 9 people or 21.43%, the moderate category was 7 people or 16.67%. External factors and internal factors play an important role in shaping the perceptions of students following physical learning at school.